Pengaruh Perilaku Konsumtif dan Gaya Hidup Terhadap Keputusan Pembelian Skincare Mahasiswi STIA Setih Setio - Fajar Ifan Dolly (STIA Bengkulu, 2022)
This study aims to determine (1) the effect of consumptive behavior on skincare purchasing decisions, (2) the influence of lifestyle on skincare purchasing decisions, (3) the influence of consumptive behavior and lifestyle on skincare purchasing decisions. The method used is causal associative research using a descriptive quantitative approach. While determining the sample using the determination of the number of samples from the population based on the theory of Isaac and Michael, with formulas and tables for determining the number of samples from the population with an error rate of 10%. So, obtained a sample of 122 respondents. The results showed (1) consumptive behavior (X1) had a significant effect on purchasing decisions (Y) for skincare at STIA Setih Setio Muara Bungo female students of 4.375. (2) Lifestyle (X2) has a significant effect on purchasing decisions (Y) skincare at STIA Setih Setio Muara Bungo female student of 1.889. (3) Consumptive behavior (X1) and lifestyle (X2) simultaneously have a low influence contribution, which is 0.363 or (36.30%) on the purchasing decision variable (Y) skincare.